2014
DOI: 10.14744/nci.2014.37450
|View full text |Cite
|
Sign up to set email alerts
|

Is there a new finding added to the fibromyalgia syndrome?

Abstract: OBJECTIVE:The aim of this study is to examine depression and anxiety related arrhytmia risk in fibromyalgia syndrome (FMS).METHODS:Fifty-nine patients with the diagnosis of FMS and 20 control participants were included in the study. Fibromyalgia Impact Questionnaire (FIQ), Visual Pain Scale (VPS) surveys were applied to determine the severity of the disease. Beck Anxiety (BAS) and Beck Depression scales (BDS) were applied to all participants. Electrocardiograms were obtained from all participants. P-wave dispe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…In a similar study, Doğru et al (10) which evaluated 50 individuals with FMS and 30 healthy controls, the prevalence of supraventricular extra systole was found as 48% in the FMS group and this ratio was found as 23.3% in the control group. Sarıfakıoğlu et al (11) have also showed that the risk of atrial fibrillation was increased in patients with FMS. In contrast to these data, Yolbas et al (13) reported similar frequencies of arrhythmias in patients with FMS when com- pared with controls.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…In a similar study, Doğru et al (10) which evaluated 50 individuals with FMS and 30 healthy controls, the prevalence of supraventricular extra systole was found as 48% in the FMS group and this ratio was found as 23.3% in the control group. Sarıfakıoğlu et al (11) have also showed that the risk of atrial fibrillation was increased in patients with FMS. In contrast to these data, Yolbas et al (13) reported similar frequencies of arrhythmias in patients with FMS when com- pared with controls.…”
Section: Discussionmentioning
confidence: 95%
“…Zamuner et al (15) indicated that disruption of neurocardiac integrity in patients with FMS have an impact on pain and quality of life. In a study where the relation between anxiety, depression and arrhythmia have been investigated in 59 patients diagnosed with FMS, higher anxiety-depression scores were obtained when compared to the control group, but its relation with arrhythmia has not been suggested (11).…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Pd and impaired diastolic functions have been shown in FMS patients [7] but there has been no study on ACT evaluations in FMS. Therefore, the aim of this study was to evaluate the left ventricular diastolic functions, the ACT and Pd in terms of AF, which may develop in patients with FMS.…”
Section: Introductionmentioning
confidence: 99%